Effects of industrial wastewater reuse for crop production: A case study in Tejgaon metropolitan area of Dhaka, Bangladesh - Roy, S; Banna, LN; Mamun, SA; Farukh, MA (Journal of the Bangladesh Agricultural University, 2014)
This study was carried out to identify the benefits, adverse effects, social acceptance and a long term impacts of industrial wastewater reuse in the Tejgaon metropolitan area of Dhaka city. Questionnaire surveys were conducted in the exposed and control sites to collect data on the farmers perception and responses regarding agricultural, economic, social and environmental health issues. The most important benefits of wastewater reuse have been found as the availability of wastewater over all seasons and economic return from reduced chemical fertilizer requirement in vegetable field. The potential risks of wastewater reuse have been found as the increased insect attacks, diseases and excessive weed problem. Farmer mentioned that long term exposure of this water stimulates crop growth rapidly but it reduces grain production dramatically. Sometimes excess wastewater used for irrigation or short-term water logging in the area eventually leads to crop damage. Interviews with the key factors indicate that a long term institutional arrangement for sustainable reuse of wastewater is not beneficial in the region. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19860 J. Bangladesh Agril. Univ. 11(2): 183-188, 2013